New aspects of non-invasive diagnosis of intestinal pathology. - N. S. Fedorova (Medičnì Perspektivi)
A comparative assessment of fecal calprotectin (FC) levels was performed in 160 patients with chronic inflammatory bowel disease (CIBD) (Crohn's disease (CD), ulcerative colitis (UC)) and irritable bowel syndrome (IBS). The results of FC in patients with CIBD and IBS were compared with the values of FC  of 31 healthy patients (control group). The mean FC level in patients with CIBD was 65.75 μg/g compared to the control group (13.72 μg/g) (p<0.05). In the group of patients with IBS, the FC level was 16.18 μg/g (p≥0.05). Significant correlation was found between the levels of FC with CIBD and FC with IBS (p<0.05). The obtained results confirmed the high diagnostic value of the method of determining fecal calprotectin in the differential diagnosis of functional and inflammatory bowel diseases.